Framing techniques for IP over fiber. - Bonenfant, P. (IEEE Network : the magazine of global information exchange)
We provide a high-level but extensive overview of the protocols and framing techniques for mapping IP packets over fiber in metropolitan, regional, and wide area fiber optic networks